Methodology for Assessment Energy Efficiency in the Industrial Sector - Neves, Fábio de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Energy efficiency (E.E.) is vital for the technological development of a country, as it is intrinsically linked to the daily lives of people, public and private institutions, being a demand for national sovereignty, in addition to having enormous potential to avoid greenhouse gas emissions. However, the reduction of energy consumption has been decreasing, a trend that has important implications for consumers, companies and the environment. The increase in EE is linked to the type of sector and contribution, which is characterized by its intensity, as in the case of the industrial sector. Specifically, Brazil is currently the sixteenth country in industrial production, with a large part of its production coming from small and medium-sized companies. The absence of methodologies for EE assessment has driven a considerable part of the industrial sector to not have a safe direction in conducting the reduction of energy consumption. Thus, this thesis has as its central objective to build a metric to assist in the assessment of energy efficiency of small and medium-sized companies in Brazil. For that, using fuzzy logic, two analyzes were built to develop an assessment of the main priorities that the company should adopt. One measure is composed of a criticality index, which describe the company's main critical points considering aspects of environmental quality, cost management and industrial management in relation to EE measures, and the second by the technological improvement index that checks the main gaps of the predominant technologies of the production system: engine, lighting system, air conditioning, air compressor, refrigeration system, heating system, ventilation system, boilers and condensers. Seven case studies of companies from different industrial sectors were analyzed, in which an energy efficiency rating range was assigned through the criticality and improvement index. The analysis point out that most of the companies are within the critical range for aspects of industrial management and very inappropriate for improvement rates. In addition to these conclusions, the model indicated which actions should be taken for companies to complement or reach the energy consumption considered satisfactory. The developed model is an important tool for decision-making in small and medium-sized companies due to the different approaches contained in its structure.

A eficiência energética (E. E.) é vital para o desenvolvimento tecnológico de um país, pois está intrinsecamente ligada ao cotidiano das pessoas, instituições públicas e privadas, sendo uma demanda por soberania nacional, além de possuir enorme potencial para evitar as emissões de gases de efeito estufa. Todavia, a redução do consumo de energia vem diminuindo, tendência que tem implicações importantes para consumidores, empresas e meio ambiente. O aumento da EE está atrelado ao tipo de setor e contribuição, que se caracteriza pela sua intensidade, como é o caso do setor industrial. Especificamente, o Brasil, atualmente, é o décimo sexto país em produção industrial tendo em sua grande parte da sua produção proveniente de pequenas e médias empresas. A ausência de metodologias para avaliação da EE tem impulsionado parte considerável do setor industrial a não ter direcionamento seguro na condução da redução do consumo energético. Desta forma, esta tese tem como objetivo central construir uma métrica para auxiliar na avaliação da eficiência energética das pequenas e médias empresas no Brasil. Para tanto, por meio da utilização da lógica fuzzy foram construídas duas análises para desenvolver uma avaliação das principais prioridades que a empresa deverá adotar. Uma medida é composta por um índice de criticalidade, que descreve os principais pontos críticos da empresa considerando aspectos de qualidade ambiental, gestão de custos e gestão industrial em relação às medidas de EE, e a segunda pelo índice de melhoria tecnológica que verifica as principais lacunas das tecnologias predominantes do sistema produtivo: motor, sistema de iluminação, ar condicionado, compressor de ar, sistema de refrigeração, sistema de aquecimento, sistema de ventilação, caldeiras e condensadores. Foram analisados sete estudos de casos de empresas de diferentes setores industriais. Em que foi atribuído, através, do índice de criticalidade e de melhoramento uma faixa de avaliação de eficiência energética. Foram avaliados sete estudos de casos com empresas de diversos setores industriais, verificando que a maioria está dentro da faixa crítica, para aspectos de gestão industrial e muito inapropriado para os índices de melhoramento. Além dessas conclusões, o modelo indicou quais ações devem ser tomadas para que as empresas complementem ou alcancem os consumos de energia considerados satisfatórios. O modelo desenvolvido mostra-se uma importante ferramenta para a tomada de decisão de pequenas e médias empresas devido às diferentes abordagens contidas na sua estrutura.
Metodologia de Avaliação de Eficiência Energética no Setor Industrial
Keywords: Energy efficiency; Small and Medium Enterprises; Fuzzy Logic; Criticality Index; Technological Gap